HOW TO TEACH RUSSIAN LANGUAGE AND LITERATURE - Usmanova Umida Abdukarimovna (American Journals, 2022)
The communicative orientation in Russian language teaching is characterized by the fact that the development of competencies and skills in verbal communication or communication is advertised as the most important learning goal. The need to connect professional courses with the child's actual language experience, the process of acquiring knowledge, is particularly difficult.
Keywords: communicative competence, preparation for intercultural dialogue, rhetoric, innovative technologies, interactive methods, pedagogical communication